Incertidumbre financiera en prácticas contables de la ferretería de la cuidad de Duitama. (2020)
In this research, an analysis will be carried out on the accounting policies and financial statements of the hardware store analyzing the accounting policies established by the company and the protocols for realizing these policies in the accounting processes, in the property elements, plant and equipment. , inventories and accounts receivable, in the same way the financial statements of the last years 2018 and 2019 will be analyzed, with the aim of comparing whether the accounting policies established by the company are being performed in the accounting processes, so that the dealer can make better decisions more clearly and reflect the reality of the financial statements.